2021
DOI: 10.1109/access.2021.3076845
|View full text |Cite
|
Sign up to set email alerts
|

Estimation Bounds of Beat Signal in the R-Mode Localization System

Abstract: The R-Mode system is a terrestrial navigation system currently under development, which exploits existing means of medium frequency radio transmission. The positioning and timing performance depends on the estimation of the signals' phase offset, from which the ranging information is derived. For an analogous problem such as the single-tone phase estimation, the Cramér-Rao bound (CRB) describes the minimal achievable performance in the mean squared error sense. For R-Mode, the problem involves the estimation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The application of the phase-correction scheme compensates the systematic bias significantly (see also the histogram of the Gross Mohrdorf range error in Figure 9). The propagation path with an increased proportion of land after entering the bay causes a larger phase delay as well as a decrease in the signal strength, which directly affects the accuracy of phase estimation [36], explaining the larger standard deviation of the range error after 8:00 GMT. The observed improvement in range level affects the position error as well.…”
Section: First Dataset: Polish Coast-29 August 2020mentioning
confidence: 99%
“…The application of the phase-correction scheme compensates the systematic bias significantly (see also the histogram of the Gross Mohrdorf range error in Figure 9). The propagation path with an increased proportion of land after entering the bay causes a larger phase delay as well as a decrease in the signal strength, which directly affects the accuracy of phase estimation [36], explaining the larger standard deviation of the range error after 8:00 GMT. The observed improvement in range level affects the position error as well.…”
Section: First Dataset: Polish Coast-29 August 2020mentioning
confidence: 99%
“…In our previous publication [18], we had shown that we can assume the Cramér-Rao lower bound (CRB) for the estimation of the phase θn of the n-th subcarrier, in the absence of a modulated signal, to be…”
Section: Efficient Estimatormentioning
confidence: 99%
“…We had shown that the modulated signal affects the accuracy of the phase-estimation of the aiding carriers when the DFT is used as maximum likelihood estimator. We assume, that this is due to the fact that the assumption of white Gaussian noise is not valid any more [17], [18]. However, this estimator is of practical relevance, as it can be implemented in a highly computational effective way [13] to estimate multiple harmonics.…”
Section: Introductionmentioning
confidence: 99%